Dissolved Gas Behavior in Natural Ester under Corona, Surface, and Internal Discharges - Jongvilaikasem, Korraya; Pattanadech, Norasage (My University, 2020)
The normal operating transformers encounter various kinds of stresses such as thermal stress, electrical stress, mechanical stress, and ambient effect that can expedite the deterioration process. Partial discharge occurs normally in high voltage equipment under high electric field. For a natural-immersed transformer, partial discharge can be detected by the dissolved gas analysis technique. This paper presents the patterns of dissolved gas generation in natural ester under partial discharge conditions. Besides, the existence of acidity number is also reported. Various types of partial discharge, including corona discharge, surface discharge, and the FR3 impregnated pressboard internal discharge, were simulated. A needle-plane electrode was used to simulate corona discharge, a needle-plane electrode with the impregnated pressboard was used to simulate surface discharge, whereas the plane electrode with pressboards was used to simulate the internal discharge. Each experiment was simulated in the test vessel under 24 kV test voltage for 3000 hours. The natural ester and the pressboards were heated at 80°C for 12 hours. before filled in the test vessel. Each test vessel was contained two identical plane electrodes with a 32 mm gap spacing. The impregnated pressboard was fit-inserted between such electrodes. The high voltage electrode was subjected to 24 kV whereas another plane electrode was grounded. Then, the natural ester were sampled from the vessel after operating for 350, 1000, and 3000 hours respectively. Dissolved gas analysis of the natural ester in this work followed ASTM D3612; the acidity number of aging natural ester was also tested according to ASTM D664. From the test results, it was found that different types of partial discharges generated various patterns of dissolved gas generation. Besides, the experiment with non-impregnated pressboards couldn't survive in this condition.
Keywords: acidity number; dissolved gas analysis; liquid insulation property; natural ester; partial discharge; transformer